Analisis Penerapan Metode User-Centered Design pada Augmented Reality (AR) dengan Marker Based Tracking - Zainil Abidin; Daniel Arsa; Yolla Noverina (Jurnal PROCESSOR, 2024)
This research investigates the use of Augmented Reality (AR) technology in the context of higher education faculty promotion. The main focus of this research is to design and test an AR application that uses a marker in the form of a QR-Code placed on the faculty study program brochure. This AR application aims to provide prospective students with an interactive experience in exploring the facilities, study programs and academic potential of the faculty. The location of the research was at the Faculty of Science and Technology, Jambi University. The method for designing faculty promotional tools in the form of AR uses the UCD (User-Centered Design) method. This research includes the design stage, AR application development, as well as functionality testing and application performance evaluation. Performance testing is carried out based on the distance between the user's device and the QR-Code marker. Performance testing aims to understand the extent to which an application can function in various usage situations. The results of this study provide in-depth insight into the potential of AR as a faculty promotion tool, considering the advantages and limitations of marker-based tracking methods. These findings strengthen understanding of how AR technology can add value to prospective student recruitment efforts and guide the development of more effective AR applications in the future